2018
DOI: 10.15560/14.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of ichthyofauna in streams of the middle and lower Tibagi river basin, Paraná, Brazil

Abstract: This study investigates the distribution and structure of the assemblages of fishes in tributaries of middle and lower sections of Tibagi river basin. The samples were conducted quarterly from December 2013 through December 2014, in 24 sampling sites of 8 tributaries. A total of 5643 individuals belonging to 44 species distributed in 13 families and 5 orders are reported. The families Characidae, Loricariidae, and Heptapteridae were predominant; Astyanax paranae, Phalloceros harpagos, Piabina argentea, Astyana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…With the predominance of Siluriformes and Characiformes, the taxonomic composition of the 24 sampled streams follows the pattern described for the Neotropical freshwater fish fauna (Castro 1999 recorded in Characidae, Loricariidae, and Heptapteridae also follows the pattern of the most species-rich families in the upper rio Paraná system (Langeani et al 2007). Similarly, several studies have indicated the prevalence of these families in other streams of this drainage system (e.g., Hoffmann et al 2015;Bifi et al 2017;Batista-Silva et al 2018;Claro-García et al 2018;Azevedo-Santos et al 2019b), especially for streams of the rio Paranapanema system, such as the rio das Cinzas (Costa et al 2013) and the rio Itararé (Cetra et al 2016) basins.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…With the predominance of Siluriformes and Characiformes, the taxonomic composition of the 24 sampled streams follows the pattern described for the Neotropical freshwater fish fauna (Castro 1999 recorded in Characidae, Loricariidae, and Heptapteridae also follows the pattern of the most species-rich families in the upper rio Paraná system (Langeani et al 2007). Similarly, several studies have indicated the prevalence of these families in other streams of this drainage system (e.g., Hoffmann et al 2015;Bifi et al 2017;Batista-Silva et al 2018;Claro-García et al 2018;Azevedo-Santos et al 2019b), especially for streams of the rio Paranapanema system, such as the rio das Cinzas (Costa et al 2013) and the rio Itararé (Cetra et al 2016) basins.…”
Section: Discussionsupporting
confidence: 57%
“…However, these projects focused mostly on larger rivers and, until recently, low-order streams (especially in the Paraná State) still lacked samplings. This scenario changed in recent years as researchers started to focus ecological and biogeographical aspects of several sub-basins of the alto rio Paraná system, increasing our knowledge about the fish species resident in its streams (e.g., Castro et al 2003;Cetra et al 2012;Cionek et al 2012;Pagotto et al 2012;Costa et al 2013;Hoffmann et al 2015;Cetra et al 2016;Frota et al 2016a,b;Larentis et al 2016;Cavalli et al 2018;Delariva et al 2018;Claro-García et al 2018;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of illegal introduction has been commonly reported, and cause increasing concern due to the invasive potential of this species, which is largely unknown to amateur aquarists (Magalhães & Jacobi, ). Ornamental aquaculture is described as an introduction vector of X. hellerii in many Brazilian river basins; as registered in streams in the state of Minas Gerais (Magalhães & Jacobi, ; Melo, Machado, Oliveira, Cruz, & Latini, ), and in the state of Paraná in the Pirapó, Tibagi (Claro‐García, Assega, & Shibatta, ; Cunico, Graça, Agostinho, Domingues, & Latini, ), and upper Paraná river basins (Gubiani, Daga, Frana, & Graça, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided important records of fish species in headwater streams of the Paraná State, but all of them are limited to the systems of the upper rio Paraná (e.g., Delariva & Silva 2013;Hoffmann et al 2015;Cetra et al 2016;Frota et al 2016a;Claro-García et al 2018) and the rio Iguaçu (e.g., Frota et al 2016b;Larentis et al 2016;Delariva et al 2018), which converges to the rio de la Plata system. Many headwater streams located in Atlantic Coastal basins of the Paraná State are unlisted and little is known about which species reside there.…”
Section: Introductionmentioning
confidence: 99%